Xenotransplantation elicits salient tumorigenicity of adult T‐cell leukemia‐derived cells via aberrant AKT activation. Issue 5 (7th April 2016) - Yamaguchi, Kazunori; Takanashi, Tomoka; Nasu, Kentaro; Tamai, Keiichi; Mochizuki, Mai; Satoh, Ikuro; Ine, Shoji; Sasaki, Osamu; Satoh, Kennichi; Tanaka, Nobuyuki; Harigae, Hideo; Sugamura, Kazuo
Abstract : The transplantation of human cancer cells into immunodeficient NOD/SCID/IL‐2Rγc null (NOG) mice often causes highly malignant cell populations like cancer stem cells to emerge. Here, by serial transplantation in NOG mice, we established two highly tumorigenic adult T‐cell leukemia‐derived cell lines, ST1‐N6 and TL‐Om1‐N8. When transplanted s.c., these cells formed tumors significantly earlier and from fewer initial cells than their parental lines ST1 and TL‐Om1. We found that protein kinase B (AKT) signaling was upregulated in ST1‐N6 and TL‐Om1‐N8 cells, and that this upregulation was due to the decreased expression of a negative regulator, INPP5D. Furthermore, the introduction of a constitutively active AKT mutant expression vector into ST1 cells augmented the tumorigenicity of the cells, whereas treatment with the AKT inhibitor MK‐2206 attenuated the progression of tumors induced by ST1‐N6 cells. Collectively, our results reveal that the AKT signaling pathway plays a critical role in the malignancy of adult T‐cell leukemia‐derived cells. Abstract : In this study we were able to generate highly tumorigenic sublines from ATL‐derived cell lines through serial xenotransplantation in immunodeficient NOG mice. We found aberrant activation of AKT signaling plays a pivotal role in the tumorigenic potential of the ATL cells.